Genes for leaf rust resistance (Lr) in Indian wheats - and D. V. SINGH, P. BAHADUR, J.B. SHARMA (Indian Phytopathology, 2002)
An analysis of 28 improved wheat lines, developed at the Indian Agricultural Research Institute, enabled identification of leaf rust (Puccinia recondita) resistance genes, Lr1, Lr3, Lr10, Lr19, Lr23, Lr24 and Lr26 alone or in various combinations. Genes Lr1 + Lr23 were identified in DW 616, SW 796 and DW 829; Lr3 in DW 832 and DW 833; Lr10 + Lr23 in DW 774; DW 809 and DW 847; Lr19 in DW 837, DW 838, CP 172, CP 173, CP 175 and CP 176; Lr10 + Lr26 in DW 839, DW 840 and DW 842; Lr23 + in DW 722, DW 777, DW 849, DW 850, DW 855 and DW 859; Lr24 in DW 831; and Lr26 was thought to be in HD 2618 and in combination with Lr23 in DW 694, DW 698 and DW 812. Diversification of resistance to leaf rust was also revealed in the Indian wheat breeding programme.